Sustainable Marketing and Strategy - Au-Yong-Oliveira, Manuel; Sousa, Maria José (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Sustainability comes in many forms and is increasingly linked to strategy and to marketing. Organizations have long since recognized the importance of corporate social responsibility and, hence, it is the upper echelon of the enterprise that is involved in the major decisions in this area. Dedicated and specialized teams are the future of organizational sustainability, and we predict that the next decade will see an exponential increase in sustainable activity and investment. Firms cannot afford to let certain opportunities pass without leaving their mark-a mark which will affect the brand and, more importantly, consumers' minds and their attitudes towards the market of products and services. The market in general will have to adapt to the circular economy and to the well-being of employees and, indeed, of society and its stakeholders, in order to prosper. We are glad to have made even a small contribution to the growing debate on green and soft issues, such as those contained in this book.